Metabolism of 3-pentanone under inflammatory conditions*Institution to which the work should be attributed: Center of Breath Research, Department of Anaesthesiology, Intensive Care and Pain Therapy, Saarland University Medical Center, Homburg (Saar), Germany. (28th September 2016) - Kleber, Astrid; Maurer, Felix; Lorenz, Dominik; Wolf, Beate; Albrecht, Frederic; Shopova, Teodora; Sessler, Daniel I; Volk, Thomas; Kreuer, Sascha; Fink, Tobias
Abstract: Breath analysis of rats using multi-capillary column ion-mobility spectrometry (MCC-IMS) revealed alterations in acetone and other ketones, including 3-pentanone, during inflammation. The alterations seem likely to result from oxidative branched-chain keto acid (BCKA) catabolism. We therefore tested the hypothesis that 3-pentanone arises during inflammation from increased BCKA oxidation in the liver with consequent accumulation of propionyl-CoA and its condensation products. Male Sprague-Dawley rats were anaesthetised and ventilated for 24 h or until death. Exhaled breath was analysed by MCC-IMS while rats were injected with low and high doses of lipopolysaccharide (LPS), tumour necrosis factor α (TNF α ), or vehicle. The exhaled 3-pentanone peak was identified by pure substance measurements. Blood was collected 12 h after treatment for the determination of cytokine concentrations; transcription enzymes for BCKA catabolism and the activity of the BCKA dehydrogenase were analysed in liver tissue by quantitative real-time PCR and western blotting. Exhaled 3-pentanone decreased in all groups, but minimum concentrations with high-dose LPS (0.24 ± 0.31 volts; mean ± SD), low-dose TNF α (0.17 ± 0.10 volts) and high-dose TNF α (0.13 ± 0.04 volts) were lower than in vehicle animals (0.27 ± 0.12 volts). At 60% and 85% survival times (svt) concentrations of exhaled 3-pentanone increased significantly in all animals treated with low-dose LPS, (svt60% 0.38 ± 0.18 volts, svt85% 0.62 ± 0.15 volts) and high-dose LPS (0.26 ± 0.28 volts, 0.40 ± 0.22 volts), as well as low-dose TNF α, (0.20 ± 0.09 volts, 0.39 ± 0.17 volts) and high-dose TNF α (0.18 ± 0.06 volts, 0.34 ± 0.08 volts), but not in vehicle rats (0.27 ± 0.12 volts, 0.30 ± 0.09 volts). BCKA catabolism was seen in the liver, with increased expression and activity of the branched-chain alpha-keto acid dehydrogenase (BCKD), lower expression of the propionyl-CoA carboxylase (PCC) subunits, and altered expression levels of BCKD regulating enzymes. Exhaled 3-pentanone may arise from altered BCKA catabolism. Our results suggest that excessive propionyl-CoA is possibly generated from BCKAs via increased activity of BCKD, but may undergo unusual condensation reactions rather than being physiologically processed to methylmalonyl-CoA by PCC. The pattern of 3-pentanone during early and prolonged inflammation suggests that reuse of BCKAs for the synthesis of new proteins might be initially favoured. As inflammatory conditions persist, substrates for cellular energy supply are required which activate irreversible degradation of excessive BCKA to propionyl-CoA yielding increased levels of exhaled 3-pentanone.